2017
DOI: 10.1126/sciadv.1701682
|View full text |Cite
|
Sign up to set email alerts
|

Prior alcohol use enhances vulnerability to compulsive cocaine self-administration by promoting degradation of HDAC4 and HDAC5

Abstract: Prior alcohol use increases vulnerability to cocaine addiction by promoting degradation of HDAC4 and HDAC5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…To this end, we first confirmed the presence of crosssensitization between WIN and cocaine only in adolescent (and not in adult) rats. Our previous studies on other "gateway" drugs, such as nicotine and alcohol (41,42), suggested that drugpriming properties are mediated by epigenetic mechanisms (e.g., HDACs and histone acetylation) in line with the epigeneticpriming hypothesis in addiction (43). In agreement with this hypothesis, we found that WIN preexposure resulted in cocaineinduced global histone hyperacetylation in the adolescent PFC.…”
Section: Discussionsupporting
confidence: 89%
“…To this end, we first confirmed the presence of crosssensitization between WIN and cocaine only in adolescent (and not in adult) rats. Our previous studies on other "gateway" drugs, such as nicotine and alcohol (41,42), suggested that drugpriming properties are mediated by epigenetic mechanisms (e.g., HDACs and histone acetylation) in line with the epigeneticpriming hypothesis in addiction (43). In agreement with this hypothesis, we found that WIN preexposure resulted in cocaineinduced global histone hyperacetylation in the adolescent PFC.…”
Section: Discussionsupporting
confidence: 89%
“…Also, given that several epigenetic mechanisms regulate transcription, it is possible that other mechanisms are contributing to gene expression, such as DNA methylation or microRNA interactions. Nonetheless, we found an association between histone acetylation and gene expression after repeated METH treatment for Hdac2 (decreased promoter H3/H4ac and mRNA levels) and Hdac4 (increased promoter H4ac and mRNA levels), which is in agreement with the proposed role of gene targets of class IIa HDACs in chronic responses to addictive drugs …”
Section: Discussionsupporting
confidence: 89%
“…It is noteworthy that increased H4ac at Hdac4 and Hdac5 after repeated METH occurred in parallel with decreased H3/H4ac at class I Hdac1 , Hdac2 , and Hdac8 . It has been proposed that behavioral responses to chronic exposure to addictive drugs may involve class IIa HDAC gene targets . HDAC4 and 5 appear to have specific roles in synaptic plasticity, memory formation, and spatial learning, and they have been implicated in cocaine reward and METH craving .…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we report that homozygous Hdac4 A778T mice on a nearly isogenic C57BL/6 background exhibit certain metabolic and behavioral phenotypes relevant to EDs in a sexdependent manner, including altered feeding and body weight, reduced motivation for palatable food and social subordination, which may be influenced by complicated environmental factors. Since HDAC4 has been implicated in many different brain functions, including learning and memory (Kim et al, 2012;Sando et al, 2012;Fitzsimons et al, 2013;Makinistoglu and Karsenty, 2015;Wu et al, 2016), neurodegeneration (Majdzadeh et al, 2008;Li et al, 2012;Mielcarek et al, 2013Mielcarek et al, , 2015Whitehouse et al, 2015;Wu et al, 2017;Federspiel et al, 2019), drug addiction (Griffin et al, 2017;Penrod et al, 2018;Gonzalez et al, 2019), PTSD (Maddox et al, 2018;Saha et al, 2019), and major depressive disorder (Hobara et al, 2010;Sarkar et al, 2014;Higuchi et al, 2016), future mechanistic investigations in homozygous Hdac4 A778T mice at molecular, cellular and circuit levels will not only provide novel insight into the neurobiological basis of an ED, but also advance our knowledge about the underlying mechanisms of other neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%